2021
DOI: 10.4028/www.scientific.net/kem.875.88
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Ablation, Thermal and Mechanical Characteristics of Phenolic Resin Reinforced EPDM Ultra-High Temperature Insulation

Abstract: The present research reports the influences of variant phenolic resin concentrations on the thermo-mechanical and ablation characteristics of ethylene propylene diene monomer (EPDM) elastomer. Backface temperature acclivity (BTA), charring rates, and insulation indexes were executed for the fabricated composite specimens. It was noticed that BTA was enhanced while linear/radial/mass ablation rates were significantly diminished with increasing concentration of phenolic resin (PR) in base matrix (elastomeric pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In Stage 3, the phenolic resin undergoes dehydrogenation and carbonization reactions, decomposing to produce small molecules such as CO 2 and CO, forming glassy carbides and cross‐linking with the silicon bonds generated by the combustion of nano‐SiO 2 , promoting the formation of the carbon layer. The state no longer changes as the temperature increases to 580°C 29,30 . Through this thermal stability test, it can be concluded that the PF/DOPO/Nano‐SiO 2 coating effectively improves the thermal stability and residual carbon rate of RPUF.…”
Section: Resultsmentioning
confidence: 86%
“…In Stage 3, the phenolic resin undergoes dehydrogenation and carbonization reactions, decomposing to produce small molecules such as CO 2 and CO, forming glassy carbides and cross‐linking with the silicon bonds generated by the combustion of nano‐SiO 2 , promoting the formation of the carbon layer. The state no longer changes as the temperature increases to 580°C 29,30 . Through this thermal stability test, it can be concluded that the PF/DOPO/Nano‐SiO 2 coating effectively improves the thermal stability and residual carbon rate of RPUF.…”
Section: Resultsmentioning
confidence: 86%
“…[3] Among various PAMs, ethylene propylene diene monomer (EPDM) is one of the best matrices owing to its high DOI: 10.1002/mame.202100665 char retention, low density, and excellent aging resistance, which are beneficial for the improvement of the payload and lifespan storage of SRM. [4][5][6][7][8][9] EPDM-based ablation materials are a type of carbonized composite that can generate a char layer during ablation, [10] endowing the virgin EPDM composites with a dense and integral shield. As the char layer directly resists the chemical erosion and mechanical denudation of the products of combustion gases, the thermal stability and strength of the char layer are key factors affecting the ablative performance.…”
Section: Introductionmentioning
confidence: 99%